PRINCIPLES OF THERAPY OF ACUTE BRONCHIOLITHIS IN CHILDREN - Азимова Камола Талатовна; Каримова Шахнозабону (TADQIQOTLAR, 2025)
Abstract. Acute bronchiolitis is one of the most common lower respiratory tract infections  in  children  and  causes  airway  obstruction  in  10%-30%  of  cases.  In  this regard, the aim of the study was to optimize the principles of therapy and enhance the prevention of recurrence of the disease. 54 children with acute bronchiolitis under the age  of  two  were  examined.  The  study  revealed  irrational  use  of  antibiotics  and incorrectly selected starting doses for children with acute bronchiolitis. Despite the existence of a large number of risk factors, in order to reduce the incidence of acute respiratory infections and bronchiolitis, breastfeeding should be recommended for at least the first 6 months of life. In case of bronchiolitis, antibiotic therapy is possible only in the presence of bacterial complications.